Appointment of forensic examinations in the course of investigation of criminal offences related to raiding (Law and Safety, 2024)
Establishment and development of the economic security of the state requires taking effective measures to counteract and minimise the negative impact of criminal offences that encroach on public relations in the areas of economic activity, legal activities of business entities, professional activities of public administration entities, etc. Among such criminal offences, much attention is paid to those with signs of raiding, i.e. those related to the unlawful takeover and seizure of property, assets of enterprises, institutions, organisations, corporate rights to them and other resources, encroachment on the rights of owners or authorised persons of business entities of various forms of ownership, etc. An important role in proving and clarifying the circumstances to be proved in these criminal offences is played by expert opinions. Given the insufficient elaboration of the issues related to the appointment of forensic examinations in the course of investigation of criminal offences related to raiding, the purpose of the article is to define the range of forensic examinations which are appointed during the pre-trial investigation of the latter, and to clarify the specifics of their appointment. To achieve this goal, the article uses a range of general scientific methods, as well as some philosophical and special research methods, in particular, analysis, synthesis, systemic and structural method, forecasting method and dialectical method.Based on the results of the analysis of the investigative and judicial practice of investigating criminal offences related to raiding, it has been found that the typical expert examinations which are appointed during their investigation are forensic technical examination of a document, forensic economic examination, and forensic handwriting examination. It has been generalised that they are appointed in every second criminal proceeding of the type under study.The author identifies the factors which should be taken into account when deciding on the necessity and expediency of appointing a forensic examination during a pre-trial investigation. The article also identifies the mistakes made by the prosecution when appointing the specified types of qualified specialised investigations. Given the nature of raiders’ actions, the processes taking place in society and in the professional activities of individual participants in social relations, the author outlines the prospects for further scientific research.
Keywords: criminal offence; raiding; forensic examination; business entity; seizure and takeover of an enterprise; forensic economic examination; forensic handwriting examination; technical examination of a document.